2015
DOI: 10.1371/journal.pone.0120347
|View full text |Cite
|
Sign up to set email alerts
|

Stromally Expressed β-Catenin Modulates Wnt9b Signaling in the Ureteric Epithelium

Abstract: The mammalian kidney undergoes cell interactions between the epithelium and mesenchyme to form the essential filtration unit of the kidney, termed the nephron. A third cell type, the kidney stroma, is a population of fibroblasts located in the kidney capsule, cortex and medulla and is ideally located to affect kidney formation. We found β-catenin, a transcriptional co-activator, is strongly expressed in distinctive intracellular patterns in the capsular, cortical, and medullary renal stroma. We investigated β-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
64
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(65 citation statements)
references
References 28 publications
(44 reference statements)
1
64
0
Order By: Relevance
“…The altered stromal cell differentiation would disrupt the renal stroma's ability to properly communicate with the neighbouring ureteric epithelium and MM. We have previously demonstrated that stromal β‐catenin modulates Wnt9b gene expression in the neighbouring ureteric epithelium . We believe that Wnt9b in the ureteric epithelium is modulated by factors in the renal stroma that are regulated by β‐catenin.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The altered stromal cell differentiation would disrupt the renal stroma's ability to properly communicate with the neighbouring ureteric epithelium and MM. We have previously demonstrated that stromal β‐catenin modulates Wnt9b gene expression in the neighbouring ureteric epithelium . We believe that Wnt9b in the ureteric epithelium is modulated by factors in the renal stroma that are regulated by β‐catenin.…”
Section: Discussionmentioning
confidence: 91%
“…We confirmed a 63% reduction of Pod1 expression in β‐cat GOF‐S mutants at E14.5 by RT‐qPCR (1.00 versus 0.37, p < 0.0001) (Figure F). Furthermore, using Pbx1 and Meis1/2, markers of all renal stromal cells , the majority of the expanded population of stromal cells in β‐cat GOF‐S kidneys did not express Pbx1 (Figures G and H) or Meis1/2 (Figures J and K). These results were confirmed by RT‐qPCR, which showed a 54% reduction in Pbx1 (WT 1.1 versus β‐cat GOF‐S 0.52, p = 0.044) (Figure I) and a 36% reduction in Meis1/2 (WT 1.01 versus β‐cat GOF‐S 0.654, p = 0.02) at E14.5 (Figure L).…”
Section: Resultsmentioning
confidence: 99%
“…Reduction in proximal tubule AGT protein levels in Foxd1 −/− kidneys may also be due to disruption of Foxd1-dependent signals that mediate the communication between the stromal and nephrogenic compartments. One potential signal may be stromally expressed β -catenin, reported to regulate the induction of nephrogenic progenitors (22). In support of this possibility, bioinformatic analyses reveal the presence of the consensus T-cell factor-binding sites in the regulatory regions of the AGT gene (23).…”
Section: Discussionmentioning
confidence: 99%
“…53 After deletion of β-catenin specifically in the kidney stroma, the fibroblasts in kidney capsule, cortex, and medulla, the expression of Wnt9b was markedly reduced in adjacent ureteric epithelial cells, suggesting the role of Wnt9b as effector downstream of β-catenin during induction of nephron progenitors. 54 It is interesting to note that Wnt9b participates in the planar cell polarity of epithelium and contributes to the size of tubular diameters. The mice with attenuation of Wnt9b exhibit randomly oriented cell divisions and significantly increase tubular diameter, which act through the noncanonical Rho/JNK pathway during kidney morphogenesis.…”
Section: Wnt Signaling and Kidney Developmentmentioning
confidence: 99%